The other side of whiteness: The Dutch Reformed Church and the search for a theology of racial reconciliation in the afterlife of apartheid - Van der Riet, Louis; Van Wyngaard, George Jacobus (Stellenbosch Theological Journal, 2022)
This article will provide an overview and analysis of developments in the Dutch Reformed Churcâ's (DRC) General Synod concerning race, racism, and racial reconciliation from 1986 until 2019. It seeks to extend the multiple accounts of the DRC's adoption and rejection of apartheid theology by tracing its further attempts at grappling with questions of racism during and after the transition to democracy, into the present. Three primary discourses are explored, namely the search for an inclusive ecclesiology, the commitment to community involvement in the reconstruction of South Africa after apartheid, and the transformation of interpersonal ethics towards greater respect and care for others. Thereafter, the article highlights four territories that remain largely unexplored within the DRC in the past quarter of a century and argues for their future exploration. These trajectories could contribute to a deeper transformation and conversion from the white Christianity historically tied to the DRC.